Pelatihan Membuat Kotak Emergency Listrik Respon Cepat Bencana Dengan PLTS Di Desa Desa Bucor wetan Kecamatan Pakuniran Kabupaten Probolinggo - Sulistiyanto, Sulistiyanto; Ahmad, Tengku; Suromo, Imam; Jailani, Ahmad; Fiqri, Ahmad (CV. Akira Java Bulu, 2025)
Bucor Wetan Village in Pakuniran District, Probolinggo Regency, is a disaster-prone area that frequently experiences power outages due to strong winds and flooding. This situation poses serious challenges to emergency response efforts, such as providing lighting, communications, and operating essential equipment. This community service activity aims to improve the community's knowledge and skills in building emergency boxes based on solar power plants (PLTS) as an alternative energy solution that can be used independently during disasters. The methods used included participatory theoretical and practical training, device assembly, field trials, simulations of utilization in disaster scenarios, and technical assistance. The training results showed a 42% increase in participants' understanding based on pre- and post-tests, as well as the successful assembly of emergency boxes capable of supplying electricity for basic needs such as LED lights and charging mobile phones for more than 6 hours. In conclusion, this activity successfully equipped the community with practical skills in utilizing renewable energy, improved disaster preparedness, and promoted energy independence based on environmentally friendly technologies at the community level.